Fertility potential in a cohort of 65 men with previously acquired undescended testes - van Brakel, Jocelyn; Kranse, Ries; de Muinck Keizer-Schrama, Sabine M.P.F.; Hendriks, A. Emile J.; de Jong, Frank H.; Hack, Wilfried W.M.; van der Voort-Doedens, Laszla M.; Bangma, Chris H.; Hazebroek, Frans W.; Dohle, Gert R. (Journal of pediatric surgery, 2014)
To evaluate testicular function in men with previously acquired undescended testes (AUDT) in whom spontaneous descent was awaited until puberty followed by orchiopexy in case of nondescent. Andrological evaluation including paternity, scrotal ultrasound, reproductive hormones, and semen analysis was performed in three groups: men with AUDT, healthy controls, and men with previously congenital undescended testes (CUDT). In comparison with controls, men with AUDT more often had significantly abnormal testicular consistency, smaller testes, lower sperm concentration, and less motile sperm. Except for more often a normal testicular consistency in men with AUDT, no differences were found between men with AUDT and men with CUDT. Also, no differences were found between men with AUDT which had spontaneously descended and men who underwent orchiopexy. Fertility potential in men with AUDT is compromised in comparison with healthy controls, but comparable with men with CUDT. This suggests that congenital and acquired UDT share the same etiology. No significant difference was found between men who had spontaneous descent and men needing orchiopexy. However, fertility potential is unknown for men after immediate surgery at diagnosis, and this should be a subject for future studies.